Good congruence between morphology and molecular phylogeny of Hadromerida, or how to bother sponge taxonomists. In: Hooper JNA (ed) Origin and Outlook. Proceedings of the 5th International Sponge Symposium 1998 - Chombard, C.; Boury-Esnault, N. (Memoirs of the Queensland Museum, 1999)
Within Demospongiae, the order Hadromerida is well defined and there is strong consensus among systematicians about its composition and validity...
Proceedings of the 5th International Sponge Conference, Brisbane 1998